نموذج مقترح لإدارة الجودة الشاملة في مؤسسات التعليم العالي بالجزائر في ضوء النماذج الرائدة - Tagrout, Mohamed; Fellah, Karima (Finance and Business Economies Review, 2018)
This research highlights the philosophy and the origins of the total quality management from a literature view. It also discusses global, Arabic and Islamic quality models that seek to excellence in higher education companies. These models include the appropriate techniques to use as tools to achieve improvement and distinction in these companies. Hence, we suggest that it is relevant for the Algerian higher education organism to benefit from these models due to the high success and excellence it has achieved, which can be done through the conception of a model that suits the environment and the capacities of Algerian higher education companies